STUDI KOMPARATIF PENINGKATAN LITERASI NUMERASI MAHASISWA ANTARA MODEL FLIPPED CLASSROOM DAN PERSONAL PROJECT - Mailani, Elvi; Gandamana, Apiek; Hudayah M, Nur; Afriadi, Putra; Ratno, Suyit (Universitas Negeri Medan, 2024)
Abstract: This study aims to assess the comparative effectiveness of the application of the Personal Project Model and Flipped Classroom on Elementary School Teacher Education students during the learning process. Field facts show that: (1) the importance of students to have literacy and numeracy skills, (2) new learning innovations can be obtained by applying the Personal Project and Flipped Classroom models, (3) increased knowledge is conditioned by lecturers as their job. This research uses a quantitative approach with Quasi Experiment. This research is useful for improving the literacy and numeracy skills of Elementary School Teacher Education students. The output of this research is a sinta article and proceedings as well as HAKI in the form of a final research report. Keyword: Personal Project , Flipped Clasroom, Literacy, Numeracy Abstrak: Penelitian ini bertujuan untuk menilai perbandingan efektivitas penerapan model Personal Project dan Flipped Classroom pada mahasiswa Pendidikan Guru Sekolah Dasar selama proses pembelajaran. Fakta di lapangan menunjukkan bahwa: (1) pentingnya mahasiswa memiliki kemampuan literasi dan numerasi, (2) inovasi pembelajaran baru dapat diperoleh dengan menerapkan model Personal Project dan Flipped Classroom , (3) peningkatan pengetahuan dikondisikan oleh dosen sebagai tugasnya. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian Quasi Experiment. Penelitian ini bermanfaat untuk meningkatkan kemampuan literasi dan numerasi mahasiswa Pendidikan Guru Sekolah Dasar. Luaran dari penelitian ini adalah artikel sinta dan prosiding serta HAKI berupa laporan akhir penelitian. Kata Kunci: Personal Project , Flipped Clasroom, Literacy, Numeracy